Analysis of Solar Power Generation Performance Improvement Techniques - Suresh, P. (IRO Journal on Sustainable Wireless Systems, 2022)
The performance of solar power generation systems broadly depends upon the effectiveness of the solar cell placed in the architecture. The performance of the solar cell may vary with respect to the heat generated over its surface. Hence different types of cooling methods are employed over the solar power generation system to improve its power efficiency. Apart from solar cell cooling method, different types of optimization techniques are also implemented to the solar power generation unit for extracting a good power output. The maximum power point tracking algorithm is one of the primary methods used for matching the generated power to reach the required power in the connected battery system. The paper analyzes the research attainments and limitations of the various cooling models employed for the solar power generation system to develop an efficient system in future.
Keywords: Effective cooling; solar cell lifespan; energy converter; maximum power point tracking; power forecasting